2008
DOI: 10.1188/08.cjon.125-130
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Yoga Into Cancer Care

Abstract: Although yoga has been practiced in Eastern culture for thousands of years as part of life philosophy, classes in the United States only recently have been offered to people with cancer. The word yoga is derived from the Sanskrit root yuj, meaning to bind, join, and yoke. This reflection of the union of the body, mind, and spirit is what differentiates yoga from general exercise programs. Yoga classes in the United States generally consist of asanas (postures), which are designed to exercise every muscle, nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…Previous studies have reported that yoga is beneficial people with cancer in managing symptoms such as fatigue, insomnia, mood disturbance, and stress, and improving quality of life (Distasio, 2008). Most yoga practices emphasize the importance of breathing and breathe regulation (Saraswati, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that yoga is beneficial people with cancer in managing symptoms such as fatigue, insomnia, mood disturbance, and stress, and improving quality of life (Distasio, 2008). Most yoga practices emphasize the importance of breathing and breathe regulation (Saraswati, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Yoga (both asanas and meditation) may be particularly beneficial for BCSs with AIAA as it is generally nonselective and could alleviate a wide range of additional cancer-related sequelae, such as psychological adjustment, which could address coping strategies for pain management.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous trials of yoga for BCSs, although they showed improved QOL, lacked sufficient objective measures of function. [18][19][20][21][22][23][24] To determine the effects of yoga on AI-related arthralgia, we proposed a pilot study to test the impact of yoga for treatment of AIAA among BCSs. The specific aims of this study were to (1) demonstrate the feasibility of recruitment and retention to a yoga trial, (2) determine the safety of the intervention, and (3) explore the effects of yoga on function, pain, and QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Small scale studies involving yoga (DiStasio, 2008), acupuncture and acupressure (Johnston et al, 2007;Molassiotis et al, 2007), massage (Cassileth and Vickers, 2004), healing touch (PostWhite, 2003) and aromatherapy, foot soak with reflexology (Stasi et al, 2003) have all demonstrated promising results. Further intervention studies with greater statistical power are required to build a larger body of evidence with more substantive conclusions.…”
Section: Complementary Therapiesmentioning
confidence: 99%